Genetic Basis of High-Pressure Tolerance of a Vibrio parahaemolyticus Mutant and Its Pathogenicity - Feng, Lifang; Xu, Minhui; Zhu, Junli; Lu, Haixia (Frontiers in Microbiology, 2022)
Foodborne pathogens with high-pressure processing (HPP) tolerance and their pathogenicity have gained considerable attention in the field of food safety. However, tolerance to pressure treatment varies among microorganisms and growth phases, and the mechanism by which Vibrio parahaemolyticus can become tolerant of HPP is currently not known. In this study, 183 strains of V. parahaemolyticus were isolated from seafood products, and one strain, C4, carried a thermostable direct hemolysin (tdh) gene. A strain, N11, which acquired from the C4 strain through adaptive laboratory evolution under HPP stress, could tolerate up to 200 MPa for 10 min. Compared with the C4 strain, the catalase and Na+/K+-ATPase activities in N11 strain were increased by about 2–3 times, and maintained an intact cell membrane structure under HPP treatment. As shown by murine infection trials, the C4 and N11 strains impacted the physiological activities of mice and damaged liver and spleen cells. Comparative genomic analysis showed that 17 nucleotides were mutated in the N11 strain, which led to sustained high expression of mlaC and mlaD genes in this strain. Knockout of these genes confirmed that they were involved in the high-pressure stress response, and also related to pathogenicity of V. parahaemolyticus. Thereby, our findings revealed a HPP tolerance mechanism of V. parahaemolyticus, and the high-pressure-tolerant strain still retained pathogenicity in mice with skin and fur pleating and lethargy, indicating the pressure-tolerant foodborne pathogens present health risks.